The climate mitigation effect of legal institutions: environmental courts and urban carbon balance - Long, Ziyang; Zhou, Junhan; Feng, Shutang (Frontiers in Environmental Science, 2025)
As climate change accelerates, the role of legal institutions in climate governance remains insufficiently understood despite extensive research on environmental regulation. This study introduces an urban carbon balance index that integrates both emissions and sinks, and exploits the staggered establishment of environmental courts in China as a quasi-natural experiment. Using a staggered difference-in-differences framework, we find that environmental courts significantly improve urban carbon balance by reducing carbon emissions and increasing carbon sinks, with the primary effect concentrated on emission reductions. Mechanism analysis suggests that environmental courts improve urban carbon balance by raising public and media awareness of environmental issues, prompting governments to prioritize environmental issues, and strengthening administrative enforcement of environmental laws. The effects are most pronounced in jurisdictions with weaker judicial foundations and higher economic growth pressures. These findings highlight that strengthening environmental judiciary can serve as a powerful institutional lever for carbon mitigation, underscoring the need not only to refine China’s legal framework but also to enhance enforcement capacity—lessons that are equally relevant for other emerging economies seeking effective climate governance.